Endothelial dysfunction in chronic kidney disease: Mechanisms, biomarkers, diagnostics, and therapeutic strategies - Ji-Hung Wang; Yu-Li Lin; Bang-Gee Hsu (Tzu Chi Medical Journal)
Endothelial cells regulate vascular tone, blood flow, coagulation, and inflammation, with heterogeneous populations serving specific roles throughout the body. In the kidney, endothelial cells maintain vascular integrity and function, contribute to filtration, and support other renal structures. Nitric oxide (NO) is a key signaling molecule that maintains vascular tone and endothelial function. It is synthesized by nitric oxide synthase (NOS) isoforms, with endothelial NOS playing a central role in vascular health. Chronic kidney disease (CKD) is characterized by reduced NO bioavailability, driven by the accumulation of endogenous NOS inhibitors such as asymmetric dimethylarginine (ADMA) and symmetric dimethylarginine (SDMA). Uremic toxins, oxidative stress, and proinflammatory cytokines contribute to a prothrombotic and proinflammatory state, contributing to endothelial dysfunction and exacerbating cardiovascular (CV) risks in CKD. Biomarkers such as ADMA, SDMA, endothelial microparticles, and soluble adhesion molecules offer insights into vascular health, while invasive or noninvasive diagnostic techniques can assess endothelial function in CKD. Effective management strategies focus on enhancing NO bioavailability, controlling oxidative stress, reducing inflammation, and optimizing dialysis to minimize uremic toxin levels. Emerging therapeutic approaches, including antioxidant therapies and endothelial progenitor cell-based interventions, show promise in preserving vascular function. A multifaceted approach to managing endothelial dysfunction is critical for mitigating CV complications and improving patient outcomes in CKD.